Development of an advanced mango picker with automatic sorting facility - Masum, Habib; Pati, Munna; Mahato, Soumen (Journal of Postharvest Technology, 2023)
Harvesting is one of the most important activities in the post-harvesting life of mango and it is the most difficult work for workers to collect the fruit without any type of damage and quality compromise. Traditional pickers are examples of very simple and easily available harvesting tools but it increases fruit damage caused by fruit fall and latex stains. It requires additional effort from operators which may cause musculoskeletal disorders. Other available automatic pickers are costly in operation, unhandy, required skilled manpower, and involve significant initial investment. This paper exercises the problems related to generally-used harvesting tools and proposes a low-cost advanced mango picker for improving harvesting techniques and reducing the harvesting losses due to latex stain, latex burn, and fruit fall. This advanced mango picker facilitates mango harvesting by cutting its stalk at a certain length. After cutting the stalk, the harvested mango passes through a collecting basin and is conveyed to the ground level by a flexible hose for automatic sorting into different packs. The entire activity from cutting of stalk to sorting and packing to different packs is a human touch-less automatic process controlled by a microcontroller. Hence, it decreases the overall harvesting time and effort.